Private-collective software business models: Coordination and commercialization via licensing - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2007)
The private-collective business models that involve both private investment incentives and the production of public goods are not well understood. This empirically oriented research uses the unique data from the software industries of five European countries (Finland, Germany, Italy, Portugal and Spain) to illuminate the patterns of private, entrepreneurial provision of software placed in the public domain. The estimation results strongly suggest that the highly restrictive GPL (General Public License) works as an efficient coordination mechanism for the (leading) developers of the OSS community and spreads particularly via the firms that have participated in the OSS development projects. The software companies supplying the OSS, instead, tend not to aim at using the GPL to coordinate the further development of their own OSS. The firms are rather the origin of more flexibly licensed OSS products though generally the software firms' OSS business strategies relate to the restrictive licensing strategy choices.
Keywords: D21; D23; L23; L86; 330; Open Source software; licensing; business strategies; Softwareindustrie; Open Source; Public-Private Partnership; Strategisches Management; Lizenzvergabe; Deutschland; Finnland; Italien; Portugal; Spanien